Mobility Handover Support in Bluetooth Low Energy Piconets Using Fog Computing Approach - Katila, Risto (My University, 2021)
IoT solutions have become ubiquitous as a consequence of new applications and research. The market for IoT solutions is expected to have formidable growth as the adoption of IoT continues, which will constitute a massive increase in devices connected to the Internet. At the same time, IoT applications have increasingly demanding requirements for wireless communication protocols such as faster throughput, energy efficiency, and secure connections. Bluetooth Low Energy (BLE) wireless technology is used in many IoT applications because of its low cost, small size, and low power consumption. However, there have been few applications and research related to supporting the mobility of BLE devices, although device mobility is inevitable in many situations. Therefore, this thesis proposes a novel Bluetooth Low Energy mobility handover approach. That not only overcomes the existing device mobility problems of IoT systems but also suits real-time applications where high data rate and low latency are required. In order to achieve a minimized latency during device mobility, fog computing has been applied. Besides, fog computing helps alleviate problems encountered in cloud computing, such as bandwidth problems when numerous IoT devices are simultaneously sending data to a remote server. In this thesis, an advanced fog-based IoT system is designed and implemented, which supports BLE device mobility. Based on the experimental results, the proposed handover achieves low latency and uninterrupted connections during mobility handovers while maintaining the energy efficiency and scalability of the system.

IoT -ratkaisut ovat yleistyneet kaikkialla uusien sovellusten ja tutkimuksen ansiosta. IoT -ratkaisujen markkinoiden odotetaan kasvavan huimaa vauhtia IoT:n käyttöönoton jatkuessa, mikä merkitsee valtavaa lisäystä Internetiin yhdistettyihin laitteisiin. Samaan aikaan IoT -sovelluksilla on yhä suurempia vaatimuksia langattomille viestintäprotokollille, kuten nopeampi tiedonsiirtonopeus, energiatehokkuus ja suojatut yhteydet. Langatonta Bluetooth Low Energy (BLE) -teknologiaa käytetään monissa IoT -sovelluksissa sen alhaisen hinnan, pienen koon ja alhaisen virrankulutuksen vuoksi. BLE -laitteiden liikkuvuuden tukemiseen liittyviä sovelluksia ja tutkimusta on kuitenkin ollut vähän, vaikka laitteiden liikkuvuus on väistämätöntä monissa tilanteissa. Siksi tässä opinnäytetyössä esitetään uutta menetelmää BLE -yhteyden siirrolle. Tämä ei ainoastaan ratkaise IoT -järjestelmien nykyisiä laitteiden liikkuvuusongelmia, vaan sopii myös reaaliaikaisiin sovelluksiin, joissa vaaditaan suurta tiedonsiirtonopeutta ja alhaista latenssia. Jotta saavutettaisiin mahdollisimman pieni viive laitteen liikkuvuuden aikana, on käytetty sumulaskentaa. Lisäksi sumulaskenta auttaa lievittämään olemassa olevia pilvilaskennan ongelmia, kuten kaistanleveysongelmia, kun lukuisat IoT -laitteet lähettävät dataa samanaikaisesti etäpalvelimelle. Opinnäytetyössä suunnitellaan ja toteutetaan edistyksellinen sumulaskentaan perustuva IoT -järjestelmä, joka tukee BLE -laitteiden liikkuvuutta. Kokeellisten tulosten perusteella ehdotetulla yhteyden siirrolla saavutetaan alhainen latenssi ja keskeytymättömät yhteydet yhteyden siirron aikana samalla kun säilytetään järjestelmän energiatehokkuus ja skaalautuvuus.
Keywords: handover, mobility, Bluetooth Low Energy, fog computing, Internet of Things